Analisis Faktor yang Mempengaruhi Permintaan Pembelian Produk Skincare Mahasiswa Universitas Negeri Surabaya - Sari, Nur Tho'atika; hanifa, nurul (Jurnal Ekonomika : INDEPENDEN, 2023)
In this research, the research is used to analyze the factors that influence the demand for interest in purchasing skin care products. In this research aims to find out what factors determine consumers,especially among students in buying skin care products, so that later it can be used as a reference by manufacturers to meet what consumers are interested in buying skin care products. The independent variables as analyzers used in this research are namely price, product quality, and product knowledge, while the dependent variable is purchasing intention. In this research using a sample of students an from the Faculty of Economics and Business, University of Surabaya. Sampling using purposive sampling strategy and data assortment is finished online by disseminating surveys. Statistical methods used in this research is logistic regression analysis. In this research, the results are part of the independent variables, namely product quality variable and product knowledge variables have a significant influence on interest in purchasing skin care, and some of the independent variables, namely the price variable does not have a significant effect on purchase intention of skin care. While the variable that has the strongest and most dominant influence in this research is the product knowledge variable.